Evaluación de un bioplástico a partir de almidones modificados provenientes de la semilla de aguacate variedad hass (Persea Americana Mil). (2022)
The objective of this work is to evaluate the characteristics of a bioplastic based on modified starches from Hass variety avocado seed (Persea americana mill). To develop this work, the raw material (avocado seed) was obtained from the company Guacamole Listo S.A.S. located south of Bogotá, Colombia. This seed underwent a pretreatment that consisted of washing, drying and removing the shell.